Strategi Kepemimpinan Kiai dalam Menumbuhkan Karakter Peduli Sosial Santri di Pondok Pesantren Al Majidiatul Misri Cigugur - Arif Rahman Aziz; Sobirin Sobirin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
The kiai's leadership strategy in fostering the character of social care is very important to be implemented in Islamic boarding schools. This study aims to describe how the kiai leadership strategy in fostering the social care character of students at Al Majidiatul Misri Cigugur Islamic boarding school. This research uses qualitative research methods, with the research subjects being the head kiai, kiai council, pesantren management and rois aam. The data collection techniques used in this study were observation, interviews, and documentation conducted directly to the field. The results of the study found that it turns out that the Kiai leadership strategy at Al Majiatul Misri Islamic Boarding School in fostering the character of social care in students through a holistic approach, with this approach, students are invited to understand the importance of social responsibility and are encouraged to actively participate in various activities that benefit the community. Kiai also implements programs that are not through routine studies alone but through programs that include the community.